Effects of sulphurous gases in two CO2 springs on total sulphur and thiols in acorns and oak seedlings - Grill, D; Müller, M; Tausz, M; Strnad, B; Wonisch, A; Raschi, A (Atmospheric Environment, 2004)
Quercus ilex and Quercus pubescens acorns were collected at two CO2 springs in Tuscany (Bossoleto and Viterbo, resp.). In addition to elevated CO2, these springs are a source of H2S and SO2 . Acorns from a comparable ﬁeld site distant from CO2 springs were used as controls. Acorns from CO2 springs contained signiﬁcantly higher sulphur concentrations than controls (0.67 vs. 0.47 mg g 1 dw in Q. ilex cotyledons and 1.01 vs. 0.80 in Q. pubescens) and, in Q. ilex, also more glutathione (1634 vs. 1393 nmol g 1 dw). When acorns were germinated and seedlings grown under ambient air conditions in the Botanical Garden in Graz for one year, leaves of Q. pubescens grown from CO2 spring acorns showed signiﬁcantly higher S-concentrations than leaves grown from control acorns (2.27 mg g 1 vs. 1.56 mg g 1 dw), and those of Q. ilex higher glutathione concentrations (929 vs. 462 nmol g 1 dw, CO2 spring vs. control acorns). One-year-old Q. ilex seedlings grown from CO2 spring acorns also showed elevated rates of chromosomal aberrations in root tips (a widely used test for environmental impacts), suggesting a permanent stress situation of the seedlings originating from the CO2 springs.
Keywords: cytogenetic; Glutathione; hydrogen sulphide; Stress; Sulphur dioxide